Pembelajaran Berkarakteristik Pembelajaran Inovatif Abad 21 pada Materi Perkembangbiakan Tumbuhan dan Hewan dengan Model Pembelajaaran Teagament Menggunakan Media Teka Teki Silang di Smp Negeri 1 Bumijawa - Dian Norma Aprillia (Cakrawala: Jurnal Pendidikan, 2022)
Learning should be designed to provide opportunities for students to be active and develop the skills needed in the 21st century. The Teams Games Tournament learning model which is abbreviated as Teamament is a cooperative learning model that is student-centred and oriented to the competencies needed in the 21st century. The research was carried out in two cycles by applying the Teams Games Tournament (Teagament) learning model with Crossword Puzzles (TTS) on the subject of Plant and Animal Reproduction Systems. Data collection techniques through learning outcomes tests, observation, and documentation. The results showed an increase in student activity and learning outcomes after the implementation of the action. The percentage of student activity increased from 40% at the end of the first cycle to 66.7% at the end of the second cycle. The percentage of students' learning completeness increased from before the action, cycle I and cycle II, respectively 36.7%, 46.7%, and 70%. It can be concluded that the application of the Teams Games Tournament (Teagament) learning model with Crossword Puzzle (TTS) media can increase the activity and learning outcomes of class IX C students of SMP Negeri 1 Bumijawa semester 1 of the 2019/2020 academic year on the subject of Plant and Animal Reproduction Systems